Earthworm species in different land use systems in the state of Goiás and the Federal District of Brazil - Ferreira, Talita; Niva, Cintia C.; Dudas, Rafaela; Roani, Rodrigo; Durães, Natália; Marchão, Robélio Leandro; James, Samuel Wooster; Bartz, Marie L.c.; Brown, George G. (Zootaxa, 2023)
The state of Goiás and the Federal District together cover an area of about 346 thousand km2, including the diversified Cerrado vegetation, also known as the Brazilian Savanna, a biodiversity hotspot with many endangered and endemic species. Much of the Cerrado has been converted to agriculture, but little is known of its earthworms, and the impacts of land use management and agricultural practices on their density and diversity. In the present paper we review the known earthworm species in Goiás and the Federal District based on historical and museum records, and update information on their distribution and populations in different counties and land use systems with data from recent samplings. Five additional species are reported here for the first time, raising the total to 12 species currently known from Goiás, from the families Benhamiidae (1), Glossoscolecidae (1), Megascolecidae (3), Ocnerodrilidae (2) and Rhinodrilidae (5). In the Federal District, an additional 10 species are reported, bringing the total to 23 earthworm species, belonging to the families Benhamiidae (4), Eudrilidae (1), Glossoscolecidae (2), Ocnerodrilidae (1), Lumbricidae (2), Megascolecidae (1) and Rhinodrilidae (12). Native species in Goiás (6) were found in areas with lesser disturbance, such as in native forest and flooded areas/river banks, a phenomenon also observed in the Federal District. On the other hand, the exotic and peregrine species found in Goiás (6) and in the Federal District (9) dominated in disturbed sites, such as perennial crops, agroforestry, annual crops, urban areas, secondary forests, pastures and agropastoral systems, among others. Given the many new species found and the extension of Goiás and the Federal District, further effort is needed to adequately characterize the earthworm fauna of the region, from where many other species are expected.